A high-conductive thermoplastic polyurethane elastomer and preparation method thereof

By using metal oxide in situ modified carbon nanofibers, the problems of insufficient conductivity of TPU and poor dispersion of conductive fillers are solved, and the dual improvement of conductivity and mechanical properties is achieved, and applications that meet high-performance requirements are met.

CN118702894BActive Publication Date: 2025-02-07HUADA CHEM GRP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411205634.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-02-07
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

The existing thermoplastic polyurethane elastomers (TPUs) have shortcomings in their conductivity, and the poor dispersion of traditional conductive fillers lead to limited improvement in conductivity and difficult to meet the high-performance requirements.

Method used

Using metal oxide in situ modified carbon nanofibers as conductive fillers, nanofibers are prepared by electrospinning technology and calcined in a high-temperature inert atmosphere to form metal oxide in situ modified carbon nanofibers to improve the conductivity of the material and Mechanical properties.

Benefits of technology

It significantly improves the conductivity and mechanical properties of TPU, achieves the dual improvement of conductivity and mechanical properties, and meets the application that requires high performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of polyurethane elastomers, and more particularly to a highly conductive thermoplastic polyurethane elastomer and a preparation method thereof. By weight, the raw materials for preparing the highly conductive thermoplastic polyurethane elastomer include the following components: 15-70 parts of diisocyanate, 30-80 parts of polyol, 3-18 parts of chain extender, 1-40 parts of metal oxide in-situ modified carbon nanofibers, 0.5-5 parts of catalysts, and 1-7 parts of other additives. The present invention introduces metal oxides in-situ into carbon nanofibers to synergistically improve the conductivity of the material. In addition, the nanofibers obtained by electrostatic spinning technology have excellent specific surface area, mechanical properties, and good interfacial adhesion with a polymer matrix, which can significantly improve the mechanical properties of the polymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyurethane elastomers, and in particular relates to a highly conductive thermoplastic polyurethane elastomer and a preparation method thereof. Background Art

[0002] Thermoplastic polyurethane elastomer (TPU) has been widely used in many industrial fields due to its excellent physical properties such as high strength, high elasticity, wear resistance and weather resistance. However, with the rapid development of electronics, communications and energy technologies, the demand for material conductivity is increasing, and traditional TPU materials have obvious deficiencies in conductivity. Therefore, the development of highly conductive TPU materials has become one of the current research hotspots.

[0003] In the prior art, there are many methods to try to improve the conductivity of TPU. For example, Chinese patent CN112724644 A discloses a conductive thermoplastic polyurethane elastomer and a preparation method thereof, wherein the conductive thermoplastic polyurethane elastomer is composed of the following raw materials in parts by weight: 25-35 parts of diisocyanate, 50-60 parts of polyester polyol, 5-15 parts of hyperbranched polyol, 1-5 parts of chain extender, 1-10 parts of epoxy group-modified multi-walled carbon nanotubes, 1-10 parts of layered silicate, and 0.5-5 parts of catalyst. It can be seen that it discloses a method of introducing conductive fillers such as epoxy group-modified multi-walled carbon nanotubes and layered silicates to synergistically improve the conductivity and mechanical properties of TPU. Although this method improves the conductivity of the material to a certain extent, the mechanical properties are still significantly reduced, which limits its application in certain occasions where high mechanical properties are required.

[0004] In the field of improving the conductivity of thermoplastic polyurethane elastomers (TPU), traditional methods mostly rely on adding conductive fillers such as carbon black, graphene, carbon nanotubes, etc., in order to achieve the purpose of improving the conductivity of the material. However, these conductive fillers face the problem of poor dispersion performance in practical applications, resulting in uneven distribution of fillers in the TPU matrix, which in turn limits the improvement of conductivity. In particular, carbon nanotubes, although they have excellent conductivity, are particularly difficult to disperse in the polymer matrix due to their high specific surface area and strong van der Waals forces between them, making it difficult to fully exert their conductivity potential. For example, Chinese patent CN 108559050 A proposes a method for enhancing the conductivity of TPU using single-walled carbon nanotubes. Although the preparation process of this method is simple and the obtained polyurethane elastomer has excellent antistatic and conductivity, due to the poor dispersion of single-walled carbon nanotubes in the polymer matrix, the improvement effect of its conductivity is limited, and it is difficult to meet the more demanding conductive applications.

[0005] In addition, simply mixing multiple conductive fillers in the preparation of TPU may improve the conductivity to a certain extent, but it is often accompanied by a significant increase in the cost of use. More importantly, this simple mixing method often cannot achieve effective synergy between the components, resulting in the comprehensive performance of the material not being significantly improved. It may even reduce the original mechanical properties of TPU, such as strength and elasticity, due to the interaction between fillers, thus limiting its application in fields with high performance requirements.

[0006] Therefore, developing a highly conductive thermoplastic polyurethane elastomer and its preparation method that can effectively solve the problem of conductive filler dispersion and achieve dual improvement of conductive properties and mechanical properties has become an important direction of current material science research. This not only requires researchers to explore new conductive fillers or modification technologies to improve the dispersion of fillers and compatibility with TPU matrix, but also requires in-depth research on the interaction mechanism between the components to achieve synergistic optimization of conductive properties and mechanical properties. Summary of the invention

[0007] In view of the above deficiencies in the prior art, the object of the present invention is to provide a highly conductive thermoplastic polyurethane elastomer and a preparation method thereof.

[0008] To achieve the above objectives, the technical solutions adopted are:

[0009] One of the purposes of the present invention is to provide a highly conductive thermoplastic polyurethane elastomer. The raw materials for preparation include the following components, by weight: 15-70 parts of diisocyanate, 30-80 parts of polyol, 3-18 parts of chain extender, 1-40 parts of metal oxide in-situ modified carbon nanofibers, 0.5-5 parts of catalyst, and 1-7 parts of other additives.

[0010] Furthermore, the method for preparing the metal oxide in-situ modified carbon nanofibers comprises the following steps:

[0011] (a) Dissolve 0.5-1 g polyacrylonitrile (PAN) or polyvinylpyrrolidone (PVP) in 10 mL DMF solution;

[0012] (b) adding 0.01-0.16 g of a metal salt to the solution obtained in step (a), and stirring the mixture under magnetic stirring at 70-90° C. for 5 h to obtain a uniform spinning precursor solution;

[0013] (c) extracting the spinning solution obtained in step (b), and spinning it using a spinning device under an accelerating voltage to obtain spinning fibers containing metal ions;

[0014] (d) pre-oxidizing the spun fibers obtained in step (c) in an air atmosphere to obtain stable nanofibers;

[0015] (e) calcining the nanofibers obtained in step (d) at a high temperature in an inert atmosphere to obtain metal oxide in-situ modified carbon nanofibers.

[0016] Furthermore, the metal salt in step (b) is one or more of ferric triacetylacetonate, indium nitrate, cobalt nitrate tetrahydrate, stannous chloride dihydrate, sodium tungstate, ammonium molybdate tetrahydrate, zirconium chloride, manganese acetylacetonate, chromium nitrate nonahydrate, cerium ammonium nitrate, manganese acetate, tetrabutyl titanate, triisopropoxy vanadium oxide, copper nitrate trihydrate, ruthenium trichloride, nickel acetate tetrahydrate, zinc nitrate, chloroiridic acid, chloroplatinic acid, bismuth nitrate, and silver nitrate.

[0017] Furthermore, the extraction in step (c) refers to taking a 10 mL plastic syringe and extracting the spinning solution obtained in step (b), the needle type used in the syringe is 19-22 G, the acceleration voltage is 10-14 kV, and the distance between the needle tip and the roller receiver is maintained at 11-15 cm.

[0018] Furthermore, in step (d), the pre-oxidation temperature is 260-280° C., the pre-oxidation time is 0.5-1 h, and the heating rate is 5-10° C. / min.

[0019] Furthermore, in step (e), the high temperature calcination temperature is 600-1200°C, the reaction time is 1-8 h, the heating rate is 5-10°C / min, and the inert gas is nitrogen or argon;

[0020] Preferably, the metal oxide in-situ modified carbon nanofibers obtained in step (e) need to be ground in a mortar until there is no particle feeling, and the particle size range is 100-800 nm.

[0021] Furthermore, the diisocyanate is one or a mixture of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), dicyclohexylmethane diisocyanate (HMDI), hexamethylene diisocyanate (HDI), 1,5-naphthalene diisocyanate (NDI), isophorone diisocyanate (IPDI), triphenylmethane triisocyanate (TTI), xylene diisocyanate (XDI), para-phenylene diisocyanate (PPDI), 3,3'-dimethylbiphenyl diisocyanate (TODI), 2,4,4-trimethyl-1,6-hexamethylene diisocyanate (TMHDI), hydrogenated XDI, hydrogenated MDI, 4,4',4''-thiophosphoric acid triphenyl triisocyanate (TPTI).

[0022] Furthermore, the polyol is any one or a combination of two of polycarbonate polyol, polycaprolactone polyol, adipic acid polyester polyol, polyoxypropylene polyol, polytetramethylene glycol polyol, copolyether polyol, polyolefin polyol, polyacrylate polyol and polymer polyol.

[0023] Furthermore, the number average molecular weight of the polyol is 500-4500.

[0024] Further, the chain extender is one or more of 1,4-butanediol, ethylene glycol, propylene glycol, methylpropylene glycol, diethylene glycol, 1,4-cyclohexanol, neopentyl glycol, 1,6-hexanediol, 1,5-pentanediol, 1,3-butanediol, hydroquinone (β-hydroxyethyl) ether, resorcinol bis (β-hydroxyethyl) ether, dihydroxyethyl terephthalate, trimethylolpropane, glycerol, ethanolamine, diethanolamine, triethanolamine, triisopropanolamine, N,N-bis (2-hydroxypropyl) aniline, 3,3'-dichloro-4,4'-diaminodiphenylmethane, 3,5-diamino-p-chlorobenzoic acid isobutyl ester, diethyltoluenediamine, 3,5-dimethylthiotoluenediammonium, 4,4'-methylenebis (3-chloro-2,6-diethylaniline), and 1,3-propylene glycol-bis (4-aminobenzoate).

[0025] Furthermore, the other auxiliary agent is at least one of an antioxidant, a dispersant, a release agent, a hydrolysis stabilizer, a lubricant, and an anti-UV agent.

[0026] Furthermore, the catalyst is one or two of a tertiary amine catalyst, an organic metal catalyst, and an acid catalyst. The organic metal catalyst is preferably an organic tin catalyst, and more preferably dibutyltin dilaurate.

[0027] A second object of the present invention is to provide a method for preparing the above-mentioned highly conductive thermoplastic polyurethane elastomer, characterized in that it comprises the following steps:

[0028] (1) adding the metal oxide in-situ modified carbon nanofibers to the chain extender and mixing them to obtain a metal oxide in-situ modified carbon nanofiber mother solution;

[0029] (2) adding polyol, other additives, catalyst and diisocyanate to obtain a mixture;

[0030] (3) The mixture obtained in step (2) is added into a twin-screw extruder, and subjected to extrusion, granulation and drying to obtain the product.

[0031] Furthermore, in step (3), the temperature of the twin-screw extruder is controlled at 120-250° C., and the screw speed is 180-220 r / min.

[0032] Furthermore, in step (3), the drying temperature is controlled at 40-80° C., and the drying time is controlled at 30-120 min.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] Both metal oxides and carbon nanofibers have good electrical conductivity. In-situ introduction of metal oxides into carbon nanofibers can synergistically improve the electrical conductivity of the material. At the same time, the oxygen functional groups of metal oxides can improve the dispersibility of carbon nanofibers in polyurethane. During the high-temperature calcination of electrospun fibers, metal oxides can also improve the electrical conductivity of carbon nanofibers through their own structure or catalytic graphitization degree. In addition, the nanofibers obtained by electrospinning technology have excellent specific surface area, mechanical properties, and good interfacial adhesion with the polymer matrix, which can significantly improve the mechanical properties of the polymer. DETAILED DESCRIPTION

[0035] The present invention is described below in conjunction with embodiments. The embodiments are only used to explain the present invention and are not used to limit the scope of the present invention.

[0036] Preparation Example 1

[0037] The present preparation example provides a metal oxide in-situ modified carbon nanofiber, wherein the metal oxide in-situ modified carbon nanofiber is obtained by the following preparation method: 1 g of polyacrylonitrile (PAN) is dissolved in 10 mL of N,N-dimethylformamide (DMF) solution, and then 0.132 g of chromium nitrate nonahydrate is added, and magnetic stirring is performed at 70°C for 5 h to obtain a uniform spinning precursor solution; the precursor solution is drawn into a plastic syringe with a 21 G stainless steel needle, and spinning is performed using a spinning device at an accelerating voltage to obtain spinning fibers containing metal ions; the spinning fibers containing metal ions are pre-oxidized at 270°C in an air atmosphere for 1 h to obtain stable nanofibers; and then calcined at 900°C in an inert atmosphere for 4 h to obtain a chromium trioxide / carbon nanofiber composite material with a diameter of 160 nm.

[0038] Preparation Example 2

[0039] This preparation example provides a metal oxide in-situ modified carbon nanofiber. The only difference from Preparation Example 1 is that chromium nitrate nonahydrate is replaced by tetrabutyl titanate. The other preparation methods are the same as Preparation Example 1, and a titanium dioxide / carbon nanofiber composite material with a particle size of 160 nm is obtained.

[0040] Example 1

[0041] This embodiment provides a highly conductive thermoplastic polyurethane elastomer. The raw materials for preparing the highly conductive thermoplastic polyurethane elastomer include the following components in parts by weight:

[0042] 40 parts of diphenylmethane diisocyanate;

[0043] 50 parts of polybutylene adipate diol;

[0044] 1,4-Butanediol 10 parts;

[0045] 6 parts of chromium trioxide / carbon nanofiber composite material;

[0046] 0.5 parts of dibutyltin dilaurate;

[0047] Antioxidant-264 0.3 parts;

[0048] Dispersant Dispex ® AA 4040 0.5 part;

[0049] Release agent MA2020E 0.4 parts;

[0050] Hydrolysis Stabilizer Stabaxol ® -1 0.3 parts;

[0051] The preparation method of the highly conductive thermoplastic polyurethane elastomer is as follows:

[0052] The chromium trioxide / carbon nanofiber composite material obtained in Preparation Example 1 is added to 1,4-butanediol, and stirred at high speed for 2 h at 110°C to finally obtain a chromium trioxide / carbon nanofiber mother liquor; the mother liquor, an antioxidant, a dispersant, a release agent, a hydrolysis stabilizer, a catalyst dibutyltin dilaurate and diphenylmethane diisocyanate are added to polybutylene adipate diol with a number average molecular weight of 1000 to obtain a mixture; the mixture is added to a twin-screw extruder at a temperature of 120°C, and the extrudate discharged from the die head is cut into oval pellets by underwater pelletizing, and then dried at 40°C for 30 min to obtain the product.

[0053] Example 2

[0054] This embodiment provides a highly conductive thermoplastic polyurethane elastomer. The raw materials for preparing the highly conductive thermoplastic polyurethane elastomer include the following components in parts by weight:

[0055] 35 parts of diphenylmethane diisocyanate;

[0056] 57 parts of polytetrahydrofuran diol;

[0057] 1,4-Butanediol 8 parts;

[0058] 6 parts of chromium trioxide / carbon nanofiber composite material;

[0059] 0.5 parts of dibutyltin dilaurate;

[0060] Antioxidant-264 0.3 parts;

[0061] Dispersant Dispex ® AA 4040 0.5 part;

[0062] Release agent MA2020E 0.4 parts;

[0063] Hydrolysis Stabilizer Stabaxol ® -1 0.3 parts.

[0064] The preparation method of the highly conductive thermoplastic polyurethane elastomer is as follows:

[0065] The chromium trioxide / carbon nanofiber composite material obtained in Preparation Example 1 is added to 1,4-butanediol, and stirred at high speed for 2 h at 110°C to finally obtain a chromium trioxide / carbon nanofiber mother liquor; the mother liquor, an antioxidant, a dispersant, a release agent, a hydrolysis stabilizer, a catalyst dibutyltin dilaurate and diphenylmethane diisocyanate are added to polytetrahydrofuran diol with a molecular weight of 1000 to obtain a mixture; the mixture is added to a twin-screw extruder at a temperature of 120°C, and the extrudate discharged from the die head is cut into oval pellets by underwater pelletizing, and then dried at 40°C for 30 min to obtain the product.

[0066] Example 3

[0067] This embodiment provides a highly conductive thermoplastic polyurethane elastomer. The raw materials for preparing the highly conductive thermoplastic polyurethane elastomer include the following components in parts by weight:

[0068] 52 parts of hexamethylene diisocyanate;

[0069] 32 parts of polyethylene glycol adipate glycol;

[0070] 1,4-Butanediol 16 parts;

[0071] 6 parts of chromium trioxide / carbon nanofiber composite material;

[0072] 0.5 parts of dibutyltin dilaurate;

[0073] Antioxidant-264 0.3 parts;

[0074] Dispersant Dispex ® AA 4040 0.5 part;

[0075] Release agent MA2020E 0.4 parts;

[0076] Hydrolysis Stabilizer Stabaxol ® -1 0.3 parts.

[0077] The preparation method of the highly conductive thermoplastic polyurethane elastomer is as follows:

[0078] The chromium trioxide / carbon nanofiber composite material obtained in Preparation Example 1 is added to 1,4-butanediol, and stirred at high speed for 2 h at 110°C to finally obtain a mother liquor of the chromium trioxide / carbon nanofiber composite material; the mother liquor, an antioxidant, a dispersant, a release agent, a hydrolysis stabilizer, a catalyst dibutyltin dilaurate and hexamethylene diisocyanate are added to polyethylene adipate glycol butylene glycol with a molecular weight of 2500 to obtain a mixture; the mixture is added to a twin-screw extruder at a temperature of 120°C, and the extrudate discharged from the die head is cut into elliptical pellets by underwater pelletizing, and then dried at 40°C for 30 min to obtain the product.

[0079] Example 4

[0080] This embodiment provides a highly conductive thermoplastic polyurethane elastomer. The raw materials for preparing the highly conductive thermoplastic polyurethane elastomer include the following components in parts by weight:

[0081] 47 parts of diphenylmethane diisocyanate;

[0082] 40 parts of polyethylene glycol adipate glycol;

[0083] 1,4-Butanediol 13 parts;

[0084] 6 parts of titanium dioxide / carbon nanofiber composite material;

[0085] 0.5 parts of dibutyltin dilaurate;

[0086] Antioxidant-264 0.3 parts;

[0087] Dispersant Dispex ® AA 4040 0.5 part;

[0088] Release agent MA2020E 0.4 parts;

[0089] Hydrolysis Stabilizer Stabaxol ® -1 0.3 parts.

[0090] The preparation method of the highly conductive thermoplastic polyurethane elastomer is as follows:

[0091] The titanium dioxide / carbon nanofiber composite material obtained in Preparation Example 2 is added to 1,4-butanediol, and stirred at high speed for 2 h at 110°C to obtain a titanium dioxide / carbon nanofiber composite material mother liquor; the mother liquor, antioxidant, dispersant, release agent, hydrolysis stabilizer, catalyst dibutyltin dilaurate and diphenylmethane diisocyanate are added to polyethylene adipate glycol butylene glycol with a molecular weight of 2500 to obtain a mixture; the mixture is added to a twin-screw extruder at a temperature of 120°C, and the extrudate discharged from the die head is cut into elliptical pellets by underwater pelletizing, and then dried at 40°C for 30 min to obtain the product.

[0092] Comparative Example 1

[0093] This comparative example provides a thermoplastic polyurethane elastomer, which is different from Example 1 only in that the chromium trioxide / carbon nanofiber composite material is not added, and the contents of other components and the preparation method are the same as those in Example 1.

[0094] Comparative Example 2

[0095] This comparative example provides a highly conductive thermoplastic polyurethane elastomer, which differs from Example 1 only in that the chromium trioxide / carbon nanofiber composite material is replaced with an equal mass of conductive carbon black, and the contents of other components and the preparation method are the same as those in Example 1.

[0096] Comparative Example 3

[0097] This comparative example provides a highly conductive thermoplastic polyurethane elastomer, which differs from Example 1 only in that the chromium oxide / carbon nanofiber composite material is replaced with single-walled carbon nanotubes of equal mass, and the contents of other components and the preparation method are the same as those in Example 1.

[0098] Table 1. Raw material composition of each embodiment and comparative example (unit: mass parts)

[0099] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Methylene diphenyl diisocyanate 40 servings 35 servings 0 47 servings 40 servings 40 servings 40 servings Hexamethylene diisocyanate 0 0 52 servings 0 0 0 0 Polybutylene adipate diol 50 servings 0 0 0 50 servings 50 servings 50 servings Polytetrahydrofurandiol 0 57 copies 0 0 0 0 0 Polybutylene adipate glycol 0 0 32 servings 40 servings 0 0 0 1,4-Butanediol 10 servings 8 servings 16 servings 13 servings 10 servings 10 servings 10 servings Chromium oxide / carbon nanofiber composites 6 servings 6 servings 6 servings 0 0 0 0 Titanium dioxide / carbon nanofiber composites 0 0 0 6 servings 0 0 0 Conductive carbon black 0 0 0 0 0 6 servings 0 Single-walled carbon nanotubes 0 0 0 0 0 0 6 servings Dibutyltin dilaurate 0.5 serving 0.5 serving 0.5 serving 0.5 serving 0.5 serving 0.5 serving 0.5 serving Other additives 1.5 servings 1.5 servings 1.5 servings 1.5 servings 1.5 servings 1.5 servings 1.5 servings

[0100] The test results of the products obtained in Examples 1-4 and Comparative Examples 1-3 are shown in Table 2.

[0101] Table 2. Test results of various embodiments and comparative examples

[0102] Performance Indicators hardness Tensile Strength Surface resistance unit Shore A / D MPa Ω Inspection methods ASTM D2240 ASTM D412 ASTM D257 Example 1 95A 50 <![CDATA[8×10 3 ]]> Example 2 65A 14 <![CDATA[7.8×10 3 ]]> Example 3 72D 50 <![CDATA[8.5×10 3 ]]> Example 4 64D 43 <![CDATA[8.2×10 3 ]]> Comparative Example 1 95A 48 Insulator Comparative Example 2 95A 49 <![CDATA[10 5 ]]> Comparative Example 3 95A 40 <![CDATA[10 5 ]]>

[0103] It can be seen from the data in Table 2 that the surface resistance of the thermoplastic polyurethane elastomer prepared by the scheme of the present invention can reach a minimum of 7.8×10 3 Ω, meeting the requirements of downstream customers for electrical conductivity.

[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A highly conductive thermoplastic polyurethane elastomer, characterized in that: The raw materials for preparation include the following components by weight: 15-70 parts of diisocyanate, 30-80 parts of polyol, 3-18 parts of chain extender, 1-40 parts of metal oxide in-situ modified carbon nanofibers, 0.5-5 parts of catalyst, and 1-7 parts of other additives; The method for preparing the metal oxide in-situ modified carbon nanofibers comprises the following steps: (a) Dissolve 0.5-1 g of polyacrylonitrile or polyvinyl pyrrolidone in 10 mL of N,N-dimethylformamide (DMF) solution; (b) adding 0.01-0.16 g of a metal salt to the solution obtained in step (a), and stirring the mixture under magnetic stirring at 70-90 °C for 5 h to obtain a uniform spinning precursor solution; (c) extracting the spinning solution obtained in step (b), and spinning it using a spinning device under an accelerating voltage to obtain spinning fibers containing metal ions; (d) pre-oxidizing the spun fibers obtained in step (c) in an air atmosphere to obtain stable nanofibers; (e) calcining the nanofibers obtained in step (d) at a high temperature in an inert atmosphere to obtain metal oxide in-situ modified carbon nanofibers; The metal salt in step (b) is one or two of chromium nitrate nonahydrate and tetrabutyl titanate; According to the ASTM D2240 testing method, the Shore hardness of the highly conductive thermoplastic polyurethane elastomer is 95A, 72D or 64D.

2. The highly conductive thermoplastic polyurethane elastomer according to claim 1, characterized in that: The pre-oxidation temperature in step (d) is 260-280° C., and the pre-oxidation time is 0.5-1 h.

3. The highly conductive thermoplastic polyurethane elastomer according to any one of claims 1 to 2, characterized in that: The diisocyanate is one of toluene diisocyanate TDI, diphenylmethane diisocyanate MDI, dicyclohexylmethane diisocyanate HMDI, hexamethylene diisocyanate HDI, 1,5-naphthalene diisocyanate NDI, isophorone diisocyanate IPDI, triphenylmethane triisocyanate TTI, xylene diisocyanate XDI, paraphenylene diisocyanate PPDI, 3,3'-dimethylbiphenyl diisocyanate TODI, 2,4,4-trimethyl-1,6-hexamethylene diisocyanate TMHDI, hydrogenated XDI, hydrogenated MDI, 4,4',4''-triphenyl triisocyanate TPTI, or a mixture of several thereof.

4. The highly conductive thermoplastic polyurethane elastomer according to claim 1, characterized in that: The polyol is any one of polycarbonate polyol, polycaprolactone polyol, adipic acid polyester polyol, polyoxypropylene polyol, polytetramethylene glycol polyol, copolyether polyol, polyolefin polyol and polyacrylate polyol, or a combination of two thereof.

5. The highly conductive thermoplastic polyurethane elastomer according to claim 1, characterized in that: The chain extender is one or more of 1,4-butanediol, ethylene glycol, propylene glycol, methylpropylene glycol, diethylene glycol, 1,4-cyclohexanol, neopentyl glycol, 1,6-hexanediol, 1,5-pentanediol, 1,3-butanediol, hydroquinone (β-hydroxyethyl) ether, resorcinol bis (β-hydroxyethyl) ether, dihydroxyethyl terephthalate, trimethylolpropane, glycerol, ethanolamine, diethanolamine, triethanolamine, triisopropanolamine, N,N-bis (2-hydroxypropyl) aniline, 3,3'-dichloro-4,4'-diaminodiphenylmethane, 3,5-diamino-p-chlorobenzoic acid isobutyl ester, diethyltoluenediamine, 3,5-dimethylthiotoluenediammonium, 4,4'-methylenebis (3-chloro-2,6-diethylaniline), and 1,3-propylene glycol-bis (4-aminobenzoate).

6. The highly conductive thermoplastic polyurethane elastomer according to claim 1, characterized in that: The other auxiliary agent is at least one of an antioxidant, a dispersant, a release agent, a hydrolysis stabilizer, a lubricant, and an anti-UV agent.

7. The highly conductive thermoplastic polyurethane elastomer according to claim 1, characterized in that: The catalyst is one or two of a tertiary amine catalyst, an organic metal catalyst, and an acid catalyst.

8. A method for preparing a highly conductive thermoplastic polyurethane elastomer according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) adding the metal oxide in-situ modified carbon nanofibers to the chain extender and mixing them to obtain a metal oxide in-situ modified carbon nanofiber mother solution; (2) adding polyol, other additives, catalyst and diisocyanate to obtain a mixture; (3) The mixture obtained in step (2) is added into a twin-screw extruder, and subjected to extrusion, granulation and drying to obtain the product.

Citation Information

Patent Citations

  • Conductive thermoplastic polyurethane elastomer and preparation method thereof

    CN112724644A

  • Conductive nanofiber and preparation method and application thereof

    CN105696110A

  • Anti-static conductive thermoplastic polyurethane elastomer and preparation method thereof

    CN108559050A